Sistem Informasi Geografis Pendataan Dan Monitoring Reklame Berbasis Android - Muhammad Venza Utama; Rina Noviana (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2021)
This study aims to (1) create an Android-based geographic information system to make it easier for field officers of the Regional Revenue Agency to collect billboards and monitor the status of billboard permits installed in their area, (2) to make designs that are attractive and easy to use by users. This study uses the waterfall method which is part of the SDLC (Software Development Life Cycle) software development method which consists of 5 stages, namely planning, design, implementation, testing, operation and maintenance. The result of this study is a geographic information system for data collection and monitoring of advertisements based on Android which was developed specifically for the implementation of data collection and monitoring of advertisements. System testing is done by the Black-Box Testing method which is a software testing method from the aspect of functional specifications. From the test results, the participants stated that the functional aspects of the application had met the specifications required by the user. Furthermore, trials were also carried out involving 5 Android smartphones with different specifications. The results of this test are that the display of the billboard data collection and monitoring application is different on each smartphone, the difference in the display is in the level of color brightness. Then the difference in application performance is also found on the type of smartphone with an Android version that is quite old.